Identificação de bactérias produtoras de compostos ativos de superfície, isoladas de sedimentos de mangue - NUNES NETO, Wallace Ribeiro (2022)
Mangroves are zones of sediment transitions, favoring the cycling of materials, associated with a high concentration of microorganisms, presenting vulnerability to anthropogenic actions. This study aimed to evaluate the capacity of the microbiota in mangrove sediments from the river Anil, in the city of São Luís - MA for the production of surface active compounds (CASs). The sediment samples were collected according to the EMBRAPA 2006 methodology, being inoculated in Bushnell Haas medium, containing 1 gram of the sample for 250ml of medium plus 3% (v/v) kerosene. Being identified by the MALDI-QTOF MS method as Pseudomonas aeruginosa, capable of producing surface active compounds, PSA39. Submitted to E24 analysis, drop scattering, thermal/pressure stability, pH variation and ionic stability. The PSA39 genome was sequenced by the Illumina – MiSeq platform and the pre-assembled genomic DNA sequences were annotated using the Prokka software. The genomic sequence obtained was analyzed by Rapid Annotation using Subsystem Technology (RAST) to identify metabolic pathways associated with hydrocarbon degradation and biosurfactant production. BLAST genome distance phylogeny method (GBDP), in addition to mean nucleotide identity (ANI). Also, the genome of PSA39 was submitted to comparative analysis by MAUVE, using other strains deposited in GenBank. Orthologous gene clusters were identified using OrthoVenn 2. In this study, approximately 32 strains of bacteria were isolated from mangrove sediment samples, of which 32 isolates 9 showed emulsifying activity (E24). E24 values ranged from 13% to 57.30% analyzed. Isolate PSA39 was selected for studies of growth and production of a biosurfactant with emulsifying activity. The maximum production of compounds with emulsifying activity occurred within 100 hours. The emulsifying activity and stability tests with the biosurfactant recovered with ethyl acetate showed E24 values ranging from 57% to 69.2% of yield, with an increase in stability at basic pHs, reaching 79%, in addition to resisting the test of pressure and temperature autoclaving. Genome analysis of the P. aeruginosa PSA39 strain by RAST indicated the presence of genetic subsystems in a total of 2062 genes, 1946 of which related to non-hypothetical proteins and 571 genes related to hypothetical proteins. The genome of P. aeruginosa PSA39 showed genes related to pathways responsible for the production of rhamnolipids as secondary metabolites, many genes were related to the degradation of aromatic and lymphatic hydrocarbons, in addition to several genes related to the production of siderophores, such as pyoverdine and pyochelin. Furthermore, the analyzes performed by RAST indicated that P. aeruginosa PSA39 has several molecular mechanisms for adaptation to heavy metals, such as the protein, cobalt-zinc-cadmium (CzcC). One hundred and fifteen unique (exclusive) groups were identified in isolate PSA39 with proteins with defined functions, associated with conjugation, cellular and metabolic processes of hydrocarbons such as alcohols and aromatics visualized by the comparative genomic analysis "orthovenns" associated with the RAST platform. The results of this work allowed to demonstrate the viability of using regional microorganisms present in mangroves for the production of surface active compounds with emulsifying activity, from different carbon sources, as they have good emulsification rates and stability against the diversity of environmental factors.